The Level of Gross Domestic Regional Product (GRDP) and Inflation: Analysis of People's Purchasing Power in North Sumatra for the 2012-2022 Period - Hotman Siboro; Penus Sinurat; Venus Situmeang; Muammar Rinaldi; Sienny (Outline Publisher, 2024)
This study aims to analyze the influence of Gross Regional Domestic Product (GRDP) and inflation rate on the purchasing power of the community in North Sumatra during the period 2012-2022. Data obtained from the Central Bureau of Statistics (BPS) of the Republic of Indonesia was analyzed using multiple linear regression with the EViews software. The results of the analysis show that GRDP and the inflation rate have a significant influence on the purchasing power of the community, with statistically significant regression coefficients. Autocorrelation, heteroskedasticity, and classical assumption tests indicate that the regression model used meets the criteria and can be considered valid. The implications of these findings can be used as a basis for formulating appropriate economic policies to improve the welfare of the North Sumatra community in the future